SOME ASPECTS OF TRAINING SOCIALLY RESPONSIBLE ENGINEERS ABROAD - Sayenko, N.; Sozykina, G.; Саенко, Н. В.; Созыкина, А. С.; Саєнко, Н. В.; Созикіна, Г. С. (Харьковский национальный автомобильно-дорожный университет, 2016)
The article gives an overview of various concepts of social responsibility abroad. It is under-lined that Ukrainian technical universities should borrow the best practices of ethical education from foreign countries. Analysis of social responsibility content and structural components as well as some ways of its development abroad is given.
НЕКОТОРЫЕ АСПЕКТЫ ПОДГОТОВКИ СОЦИАЛЬНО ОТВЕТСТВЕННЫХ ИНЖЕНЕРОВ ЗА РУБЕЖОМ
ДЕЯКІ АСПЕКТИ ПІДГОТОВКИ СОЦІАЛЬНО ВІДПОВІДАЛЬНИХ ІНЖЕНЕРІВ ЗА КОРДОНОМ
Keywords: social responsibility; future engineer; professional training; foreign experience; социальная ответственность; инженер; опыт зарубежных стран; соціальна відповідальність; інженер; досвід зарубіжних країн; 378.147